Pengaruh Profitabilitas Terhadap Kebijakan Dividen PT. INDOFOOD SUKSES MAKMUR INDONESIA, Tbk di Bursa Efek Indonesia (BEI) - Nurnilasari, Nunung (Exchall, 2019)
Profitability is an important factor in determining dividend policy. Profitability itself is a ratio to assess a company's ability to seek profits. Dividends are management policy implications as outlined in dividend policy. This study aims to determine whether there is an effect of profitability on dividend policy on the company PT Indofood Sukses Makmur Indonesia, Tbk on the Indonesia Stock Exchange. This research is a descriptive analysis. The method used in this study is a quantitative method. The type of data used is secondary data in the form of financial statements. The sampling technique in this research is probability (X) and dividend policy (Y). The method of analysis by testing the classical assumptions and knowing how much the influence of independent variables and the dependent variable is done by a regression test. The data were analyzed using the SPSS 23.00 for windows program. The results showed that the profitability variable had no significant effect on the policy variables on the company PT Indofood Sukses Makmur Indinesia, Tbk on the Indonesia Stock Exchange (IDX).